Emerging role of hypoxia-inducible factor-1α in inflammatory autoimmune diseases: A comprehensive review - Tang, Yang-Yang; Wang, Da-Cheng; Wang, You-Qiang; Huang, An-Fang; Xu, Wang-Dong (Frontiers in Immunology, 2023)
Hypoxia-inducible factor-1α (HIF-1α) is a primary metabolic sensor, and is expressed in different immune cells, such as macrophage, dendritic cell, neutrophil, T cell, and non-immune cells, for instance, synovial fibroblast, and islet β cell. HIF-1α signaling regulates cellular metabolism, triggering the release of inflammatory cytokines and inflammatory cells proliferation. It is known that microenvironment hypoxia, vascular proliferation, and impaired immunological balance are present in autoimmune diseases. To date, HIF-1α is recognized to be overexpressed in several inflammatory autoimmune diseases, such as systemic lupus erythematosus (SLE), rheumatoid arthritis, and function of HIF-1α is dysregulated in these diseases. In this review, we narrate the signaling pathway of HIF-1α and the possible immunopathological roles of HIF-1α in autoimmune diseases. The collected information will provide a theoretical basis for the familiarization and development of new clinical trials and treatment based on HIF-1α and inflammatory autoimmune disorders in the future.